Chile : Report on Observance of Standards and Codes-Fiscal Transparency Module; Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper presents an update to the Report on the Observance of Standards and Codes on Fiscal Transparency for Chile. Chile has completed the first stage of the migration of its fiscal statistics to the IMF's Government Finance Statistics Manual (GFSM 2001). A main result of this migration is the production of the operating statement, corresponding to flow transactions, for the central government, the general government, and the consolidated public enterprises. However, the treatment of interest payments on inflation-indexed bonds and on debt owed to the central bank differs from that in GFSM 2001.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet